Optimalisasi Komitmen Relational Melalui Citra Lembaga, Kepercayaan Dan Kualitas Layanan (Studi pada Mahasiswa Perguruan Tinggi Swasta di Jawa Tengah) - S U P A R J O Suparjo (FEB UNTAG Semarang, 2017)
For service firms, relationship commitment and relationship outcomes have been essential for successful long-term relationship. This study is purposed to identify the impact of corporate image, service quality, students’ trust towards students’ relational commitment in University of 17 Agustus 1945 Semarang. Two-step approach to structural equation modeling was used to test the proposed model. The sample used in this study is 300 respondents. It was taken by applying proportional random sampling. There are several findings from this study: (1) the first hypothesis is accepted, which means that there is a significant and positive influence between service quality towards students’trust ; (2) the second hypothesis is accepted indicating that there is a significant and positive influence between corporate image towards students’ trust; (3) the third hypothesis is accepted which shows that there is a significant and positive influence between service quality towards students’ relational commitment ; (4) the fourth hypothesis is accepted meaning that there is a significant and positive influence between corporate image towards students’ relational commitment); and (5) the fifth hypothesis is accepted, which means that there is a significant and positive influence between students’ trust towards students’ relational commitment.